Estudio de factibilidad para la creación de una microempresa procesadora de embutidos, a base de carne de res y verduras “CHORIKIDS” (2014)
The present study has as aim demonstrate the feasibility of the creation of a company dedicated to the manufacture of meats processed with vegetables, characterized by the high value perceived of his products and directed principally the colleges public and deprived of the commune 07 of Santiago of Cali. That was going as name "CHORIKIDS". The study of feasibility is structures. The study of feasibility is structured by chapters of the following way: The First Chapter, in which the most relevant aspects of the investigation are identified. The second chapter, it includes the general aspects of the socioeconomic environment, the environments of the macro are analyzed set like they are the political, economic, technological, environmental and juridical factors; as for the third chapter the market research was approached. In the fourth chapter, the technical study is realized, where there decides location, engineering, organization of the company, legal aspects and environmental aspects. The fifth chapter, Study of the organization, legal and environmental aspects of the project, there were identified the legal processes that the company must constitute to carry out his creation. Sixth chapter, Finality Study presupposed of investments, costs of production, income, financial statements, financial evaluation and the seventh chapter, conclusions and recommendations.